Faktor-faktor yang Memengaruhi Keputusan Masyarakat dalam Memilih Wakaf Uang - Irfany, Mohammad Iqbal; Albajili, Abi Nubli; Nurhalim, Asep (Badan Wakaf Indonesia, 2022)
Wakaf Hasanah is one of the services offering by BNI Syariah (now Bank Syariah Indonesia) to collect cash waqf transactions. offers a service called “Wakaf Hasanah” throuh website and mobile phone’s application that aims to make people easier having cash waqf’s transactions. Total of waqf funds that collected through Wakaf Hasanah as much as 1.2 percent is a cash waqf funds and 98.8 percent is a waqf through money funds. This research study aims to analyze the factors that affect people’s decision in selecting cash waqf in Wakaf Hasanah. This research study used primary data from 70 randomly respondents who had done cash waqf with Wakaf Hasanah or had not done waqf. The result of this study used logistic regression method and descriptive analysis shows that comprehension on cash waqf, information access, simplicity to donate cash waqf, and people’s trust affect people’s decision in selecting cash waqf.